The future of EU cohesion: Effects of the twin transition on disparities across European regions - Ambre Maucorps; Roman Römisch; Thomas Schwab; Nina Vujanović (The Vienna Institute for International Economic Studies (wiiw), 2023)
Closing the prosperity gap between regions has always been a key political aspiration of the European Union - and cohesion policy is the primary means to achieve that goal. Europe is currently undergoing a digital and green transition that is drastically changing the way its economy works. How well prepared are regions to capitalise on the twin transition? And what impact will it have on regional cohesion in Europe? Our study finds that greening and digitalising the economy will likely widen the gap between rich and poor regions in Europe
Keywords: R11; O21; 330; EU; EU regions; regional development; digitalisation; green transition; cohesion